Guideline for Walking Tracks Development in Recreational Areas - Parisa Rafiani Khachak; Marjan Mohammadzadeh; Seyed Hamed Mirkarimi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2013)
Walking tracks are primary recreation resource facilities on which recreation activities are executed. Also, they are considered as a liaison between visitors and nature. The main purpose of this study is to provide suitable guidelines for management and development of walking tracks. Therefore, a field survey using GPS receivers was conducted to collect the required data regarding environmental conditions, characteristics of the place, and the recreational facilities existing on the area. Afterwards, data were analyzed with ArcGIS9.3 to provide a final map of the area’s walking tracks. Despite of visitors' high use of the walking tracks, results show no facilities such as signage along the tracks. Evidently, unsuitable management of the walking tracks of recreation areas, like this case, ends up in a variety of environmental negative impacts, and also decreases the quality of visitor’s recreational experience. Investigation of the walking tracks with regard to their geographic location, distance, time required to finish the tracks, and the facilities and attractions along the way, can serve as a pattern for development and better management of these tracks. By showing walking tracks investigation method, this research tries to provide a suitable model for better management of recreational areas and increase in visitors' recreational experience quality.